A new decision guidance tool for the adoption of energy retrofit solutions in historic buildings. Issue 1 (October 2021) - Rieser, Alexander; Leonardi, Eleonora; Haas, Franziska; Pfluger, Rainer
Abstract: Energy retrofit of historic buildings often represents a challenge for owners and practitioners due to the lack of knowledge and access to suitable solutions. The growth of awareness and interest in sustainability has caused an increase in the number of solutions available for improvement of historic buildings' energy performance. What it is still missing is their dissemination across the involved stakeholders. This will improve practitioners' trust on these solutions and the adoption by owners in the building renovation. In the framework of IEA SHC Task 59 and the Interreg project ATLAS, experts have collected well established and innovative solutions for historic building renovation presented in an online decision guidance tool. The set of solutions is structured in four groups: wall insulation, window solutions, solar systems and HVAC systems. For each group a decision tree was developed to guide the end-user with questions to the appropriate solutions for their building. The tool aims to inspire and motivate technicians and owners with a large number of possible solutions, which serve as a basis for further investigation and planning. With more than 130 documented solutions it is already a comprehensive tool that can be used as basis and extended in future.